Semantic of Banjarese Prepositions: Cognitive Semantics - Noor Amalia Utami; Sailal Arimi (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2021)
Spatial system is fundamental in any language. This makes each language has spatial system which in some extent distinctive one another. Study of spatial system commonly found within cognitive linguistics area which takes preposition as object of study as the present research does. Banjarese, as one of local languages in Indonesia, indicates a unique spatial system by having particular spatial particles. Data collection is based on the questionnaire where the respondents are 153 native Banjareses. The result shows that Banjarese have eight spatial prepositions which classified into three categories based on the vector direction. Preposition di, where it is used excessively, is a placement preposition where there is no movement in the configuration. On the other hand, source and goal directive preposition carry vector from and toward the LM respectively. Source-directive prepositions are di, dari, matan, and pada. Meanwhile, goal-directive prepositions are ka, taka, baka, and ampah. Particular spatial expression such as hulu (upstream), hilir (downstream), laut (sea), and darat(land) are found generated from river life. All these four spatial particles are based on river stream direction. Hulu and hilir take horizontal relation toward river while laut and darat are perpendicular to river line that extends further or nearby toward river.